Sheep Farming in Assam: Harnessing Indigenous Potential for Sustainable Development and Needed Policy Interventions - Bhattacharyya, H. K.; Borah, Probodh (International Journal of Bio-resource and Stress Management, 2026)
This paper emphasized the need for targeted scientific research, development of comprehensive management practices, and the adoption of improved strategies to boost productivity and income. Sheep farming played a vital role in supporting the livelihoods of small and marginal farmers, as well as landless labourers, by providing meat, wool, and skin as reliable sources of income. In India, sheep were mainly reared for meat and wool and were valued for their adaptability, lower feed requirements, and higher production efficiency compared to large ruminants. Despite these benefits, sheep rearing in Assam remained underdeveloped and largely traditional, with farmers practicing extensive grazing methods with minimal scientific interventions. The total sheep population in Assam has fluctuated, declining from 5.11 lakhs in 2012 to 3.32 lakhs in 2019, while the sector continued to face challenges such as lack of husbandry and veterinary care, improper breeding programs, and absence of structured farming packages. Moreover, most sheep were indigenous and unregistered, which limited their genetic improvement and productivity. Data from Assam highlighted issues such as lack of awareness, parasitic infestations, and inadequate infrastructure but at the same time there were signs of growth in sheep meat production. It goes without saying that state’s agro-climatic conditions offered significant opportunities for large scale sheep rearing. With proper planning, genetic improvement, and efficient feed management, sheep farming in Assam could become a sustainable and economically viable livelihood option, helping to reduce poverty and uplift rural communities.